Survey of Large Contiguous Blocks of Saline and Alkali Soils in the Indian Gangetic Alluvium of Uttar Pradesh - Yadav, J S P; Agarwal, R R (Journal of Soil and Water Conservation, 2022)
Despite a great advancement made in agriculture in recent years, it is a matter of grave concern that extensive areas are still lying idle due to the presence of alkali in some form or the other. This is chiefly attributable to the fact that very few concerted scientific efforts have been undertaken on a large scale by the private agency or the Government employivyg most ap- propriate management practices depending on the nature of the soil. Before such programmes are carried out successfully, it is however essential that contiguous compact areas of saline alkali lands constituting large blocks should be first demar- cated and classified on the basis of soil characteristics into different use categories ranging from the land unfit for all purposes to the land fit for agricultural production, so that every land may be put to the use to which it is best suited and be treated according to its rquirement.